Normal joint mobility in mitral valve prolapse. Issue 1 (February 1983) - Marks, J. S.; Sharp, J.; Brear, S. G.; Edwards, J. D.
Abstract : Thirty-seven adults (19 male, 18 female) with mitral valve prolapse (MVP) were examined for evidence of joint hypermobility scored on a 0-9 scale. None of the patients had hypermobility scores exceeding 3, and comparison with 37 healthy age and sex matched controls recruited from hospital staff failed to show an increased prevalence of hypermobility in MVP. There was no evidence that the MVP syndrome is a forme fruste of a heritable disorder of connective tissue.